1997
DOI: 10.1002/(sici)1099-1565(199703)8:2<78::aid-pca335>3.3.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

High Pressure Liquid Chromatographic Analysis of Polyphenols in Leaves of Eucalyptus camaldulensis, E. globulus and E. rudis: Proanthocyanidins, Ellagitannins and Flavonol Glycosides

Abstract: Polyphenols of adult leaves from Eucalyptus globulus, E. camaldulensis and E. rudis grown in Spain, in two areas with different edaphoclimatical characteristics, were estimated by chemical methods and by high pressure liquid chromatography. Leaf extracts consisted mainly of proanthocyanidins, ellagitannins and flavonol glycosides. Knowledge of the ellagitannins allows the discrimination of the three species, with E. globulus being well differentiated from the other two. However, the pattern of flavonol glycosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…For the three assays, crude extract displayed the strongest antioxidative activity that was significantly (p<0.05) different from those of its fractions and the tested standards. Activities of all extracts are probably due to the presence of polyphenols especially hydrolyzable tannins which have been previously reported in E. globulus (Cadahia et al, 1997;Hou et al, 2000;Amakura et al, 2009). Eyles et al (2004) reported that antioxidative activity of wounded wood of E. globulus extracts is due to hydrolyzable tannins including pedunculagin, di-, tri-and tetragalloylglucose.…”
Section: H 2 O 2 Assaysupporting
confidence: 56%
See 1 more Smart Citation
“…For the three assays, crude extract displayed the strongest antioxidative activity that was significantly (p<0.05) different from those of its fractions and the tested standards. Activities of all extracts are probably due to the presence of polyphenols especially hydrolyzable tannins which have been previously reported in E. globulus (Cadahia et al, 1997;Hou et al, 2000;Amakura et al, 2009). Eyles et al (2004) reported that antioxidative activity of wounded wood of E. globulus extracts is due to hydrolyzable tannins including pedunculagin, di-, tri-and tetragalloylglucose.…”
Section: H 2 O 2 Assaysupporting
confidence: 56%
“…Phenolic compounds extraction in plant materials is influenced by their chemical nature, the extraction method employed, sample particle size and storage time (Naczk and Shahidi, 2004). As reported in the literature, major compounds of E. globulus plant are hydrolyzable tannins and flavonol derivatives (Cadahia et al, 1997;Conde et al, 1997;Atoui et al, 2005). So, we used aqueous acetone (70%) as extraction solvent which is found to be better for the extraction of tannins (Cork and Krockenberger, 1991) and flavonoids (Cowan, 1999).…”
Section: Moisture Content Of Plant Materials and Extraction Yield Of Cmentioning
confidence: 97%
“…, 6 ). These flavonols derivatives have already been described in Eucalyptus species (Cadahia et al ., ; Conde et al ., ; Santos and Waterman, , ; Atoui et al ., ; Amakura et al ., ; Boulekbache‐Makhlouf et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Red gum leachate contains over 90 chemical compounds, some of which are toxic to aquatic organisms (Hillis ; Cadahía et al. ; Conde et al. ; Farah et al.…”
Section: Introductionmentioning
confidence: 99%